Cadmium Concentrations in New Zealand Pastures: Relationships to Soil and Climate Variables. Issue 3 (1st May 2014) - Reiser, René; Simmler, Michael; Portmann, Denise; Clucas, Lynne; Schulin, Rainer; Robinson, Brett
Abstract : Cadmium (Cd) is a nonessential element that occurs at above‐background concentrations in many New Zealand (NZ) soils. Most of this Cd is due to the historical application of single superphosphate that was made from Nauru phosphate rock containing between 400 and 600 mg Cd kg −1 P. Pasture Cd uptake exacerbates the entry of Cd into animal products. We sought to determine the critical environmental factors affecting Cd uptake in NZ pastures and to calculate the likely Cd intake of sheep and cattle. We tested 69 pastures throughout NZ for a range of variables, including Cd. Soil Cd and pasture Cd were positively correlated with soil P and soil concentrations of other elements found in phosphate fertilizers. We found that no single environmental variable adequately predicted pasture Cd uptake. Nevertheless, pseudo‐total soil Cd and Cd extracted using a 0.05 mol L −1 Ca(NO3 )2 solution were positively correlated with pasture Cd. Although soil pH, soil Fe, and soil Cd provided an excellent predictor of the Ca(NO3 )2 –extractable soil Cd fraction, regression models explained just 38% of the variation of the Cd concentration in pasture grasses. Incorporating the effect of pasture species composition is a crucial next step in improving these models. A calculation of the likely exposure to Cd of sheep and cattle revealed that no pastures tested resulted in sheep and cattle ingesting Cd at a rate that would result in breaching muscle‐tissue food standards. For offal products, which the NZ meat industry does not sell for human consumption, food safety standards exceedence was calculated in a few cases.